Evolving Nonlinear Multigrid Methods With Grammar-Guided Genetic Programming - Parthasarathy, Dinesh; Schmitt, Jonas; Köstler, Harald (GECCO 2023 Companion - Proceedings of the 2023 Genetic and Evolutionary Computation Conference Companion, 2023)
We formulate a formal grammar to generate Full Approximation Scheme multigrid solvers. Then, using Grammar-Guided Genetic Programming we perform a multiobjective optimization to find optimal instances of such solvers for a given nonlinear system of equations. This approach is evaluated for a two-dimensional Poisson problem with added nonlinearities. We observe that the evolved solvers outperform the baseline methods by having a faster runtime and a higher convergence rate.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Code Generation; Grammar-Guided Genetic Programming; Nonlinear Multigrid Methods